A new chronology of Peruvian neoliberalism: an alternative methodological approach - Castillo García, César (2025)
This article proposes a methodological framework and a new chronology of “waves of neoliberalism” aimed at understanding the history of Peruvian neoliberalism. First, a brief history of the term “neoliberalism” is offered in the European context, as well as its relationship with the Walter Lippmann Colloquium and the first meeting of the Mont Pèlerin Society. Subsequently, the definition of neoliberalism employed in this study and the interpretive framework that articulates actions, ideas, institutions, and distributive results are presented. These elements constitute the chronology of Peruvian neoliberalism presented in the final part of the article, which covers the period 1948-1993.